The Diurnal Changes of Hepatic Enzymes and Metabolites of Methionine Metabolism in Laying Hens - Cao, T.; Weil, J.T.; Maharjan, P.; Lu, J.; Coon , C.N. (International Journal of Poultry Science, 2020)
Background and Objective: The requirement of sulfur amino acids for laying hens have been determined but the method in which methionine is regulated has not been studied. The aim of this research was to study the hepatic methionine-metabolizing enzymes and metabolites in laying hens. Materials and Methods: Five hundred forty Dekalb-XL laying hens were housed and fed a control diet until sampling. On day of sampling, six hens were sacrificed at each time period to allow for determination of hepatic enzymatic activities and metabolite concentrations during light and dark periods. Data was analyzed using the general linear models (GLM) procedure with statistical analysis software (SAS). Results: The enzymes and metabolites showed cyclical changes related to light and dark periods. During the light period of the day, layers showed elevated activities of methionine s-adenosyltransferase (EC 2.5.1.6; MAT), cystathionine ß-synthase (EC 4.2.1.22; CS) and cystathionase (EC 4.4.1.1; C-ase) and depressed activities of betaine-homocysteine methyltransferase (EC 2.1.1.5; BHMT) and N5methyltetrahydrofolate-homocysteine methyltransferase (EC 2.1.1.13; MFMT), as compared to the dark period of the day. The hens also had a decreased methionine to cysteine ratio (Met/Cys ratio), an increased methylation ratio (s-adenosylmethionine to s-adenosylhomocysteine ratio; SAM/SAH ratio) and an increased cystathionine (CYST) concentration in the liver during the light period. Conclusion: The changes of the enzymatic activities and metabolite concentrations suggest that the methionine metabolism of laying hens during the light period was in favor of methionine degradation through cysteine synthesis. Alternatively, the metabolism of hens during the dark period was in favor of methionine conservation by limiting the conversion of methionine to cysteine. Thus, feeding hens a higher cysteine diet several hours before lights are turned off may prove beneficial to counteract the limited cysteine synthesis from dietary methionine during the dark period of the day.